Pengaruh Program Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Karyawan Dimediasi Kepuasan Kerja Karyawan Pada PT Shindengen Indonesia - Setiawati, Eka; Setyaningrum, Retno Purwani (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze the effect of health-focused Occupational Safety and Health (OHS) programs on employee productivity, as well as the mediating role of employee job satisfaction in the relationship. The study was conducted PT Shindengen Indonesia involving 87 employees as respondents with the calculation of the sample size using the Slovin formula. Data were collected through questionnaires and analyzed using SmartPLS 3.0. The results showed that the health-focused OHS program has a positive and significant effect on employee productivity, job satisfaction has a positive and significant effect on employee productivity and in addition, job satisfaction was shown to partially mediate the relationship between health-focused OHS programs and employee productivity